Chaos control of Lorenz systems using adaptive controller with input saturation - Yau, Her-Terng; Chen, Chieh-Li (Chaos, solitons and fractals, 2007)
This paper presents an adaptive sliding mode control scheme for Lorenz chaos subject to saturating input. The state of Lorenz system can be asymptotically driven to an equilibrium point in spite of the presence of input saturation and external disturbance using the proposed control scheme. Numerical simulations demonstrate the effectiveness of its application to chaotic system control. It also shows that the settling time will be decreased, if the saturation bound of control input is relaxed.